The strategic role in enhancing prestige: An exploratory study for a sample of workers in the Directorate of Education in Najaf - et. al., Mustafa Hassan Karim, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Contemporary administrative thought has been replete with a number of modern topics imposed by the environment of successive innovations, especially in the mid-nineties of the last century and the beginning of this century, and among these topics are: (strategic adaptation, organizational prestige). Despite the strenuous and accepted research efforts in the interpretation of these topics and the analysis of their intellectual contents, and their relationships, as will be clear from the presentation of the cognitive efforts, there are a number of cognitive issues that still need further research and investigation, which can be formulated as follows: What are the philosophical foundations and conceptual foundations Topics (strategic adaptation, organizational prestige) and its variables? The importance of the study was that it dealt with the strategic adaptation variable as an important tool in enhancing organizational prestige in business companies. In other words, this study is not limited to strategic adaptation only, but also deals with the extent of its impact on determining the levels of organizational prestige in the surveyed directorate. The study adopted a random sampling method in order to be able to achieve its objectives, as the sample size was (100) employees from the Najaf Directorate of Education. The study also sought to test a number of main and sub-hypotheses related to the relationships of influence and correlation between the study variables, and several statistical programs were used. (Excel 2010, Spss v23) for the purpose of data processing. The study reached a number of conclusions, including “the high level of importance for the study variables (strategic adaptation, organizational prestige) as well as the effect of strategic adaptation in enhancing organizational prestige in the study community.